CFD SIMULATION OF PASSIVE VORTEX GENERATOR ON SEPARATED FLOW DIFFUSER - Halim, Mohd Faizal; Ahmad, Kamarul Ariffin (2012)
The passive vortex generator is a simple and economic flow control device which has shown great potential to solve flow separation problem. In this work, the sub boundary layer vortex generator performance in asymmetrical diffuser of 45 degree angle has been simulated using computational fluid dynamics SST k-w turbulence model was employed to capture the turbulence separation at Reynolds number of 1.1x10 based on flat wall length. The diffuser domain consists of three sections namely inlet, expansion and outlet section. To ensure the fully developed flow at upstream of the diffuser, the inlet section height was fixed to 20 mm. The expansion section was designed with 8.5:1 ratio and diffuser total lengths were equal to 3.2 m. The vortex generator performance has been analyzed based on the effect of varying on height, generator spacing ratio and streamwise position in the diffuser. As a result, the vortex generator height shows strong correlation with separation point. While the device spacing and its position show a positive effect in reducing the reverse velocity amount as well as separation region. The optimized configuration of the vortex generator in the diffuser has been identified as the device height of 4 mm with 2.4 spacing ratio and being placed closed to the expansion section entrance